Leasing środków trwałych w Polsce i na świecie : perspektywy rozwoju - Niedzielski, Witold (The Leasing of Fixed Assets in Poland and on World : Perspective of Development, 2005)
This article presents comparative analysys of extent lease transactions in Poland and over the world. In particular some obstacles of lease developement in Poland and its perspectives for the future progress short before Poland will join European Union are indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 276-282